Direct thromboaspiration efficacy for mechanical thrombectomy is related to the angle of interaction between the aspiration catheter and the clot. (23rd September 2019) - Bernava, Gianmarco; Rosi, Andrea; Boto, José; Brina, Olivier; Kulcsar, Zsolt; Czarnetzki, Christoph; Carrera, Emmanuel; Schaller, Karl; Lovblad, Karl-Olof; Machi, Paolo
Abstract : Background: Direct thromboaspiration has been reported as an effective mechanical treatment for acute ischemic stroke. We aimed to determine whether the angle of interaction between the aspiration catheter and the clot affects the success of clot removal in ischemic stroke patients with large vessel occlusion in the anterior and posterior circulation. Methods: All patients treated at our institution by direct thromboaspiration as a firstline technique between January 2016 and December 2017 were enrolled in the study. We retrospectively reviewed baseline and procedural characteristics, the angle of interaction formed between the aspiration catheter and the clot, the modified Thrombolysis in Cerebral Infarction score, and the 3 month modified Rankin Scale score. Results: 85 patients underwent direct thromboaspiration as the firstline treatment during the study period. 100 direct thromboaspiration passes were performed. An angle of interaction of ≥125.5° significantly influenced the success of clot removal (P<0.001) with good sensitivity and specificity, in particular for occlusion of the middle cerebral and basilar artery. The combination of aspiration with a stent retriever based thrombectomy was a valid rescue treatment in cases of standalone direct thromboaspiration failure. Conclusions: In our series, an angle of interaction between the aspiration catheter and the clot of ≥125.5° was significantly associated with successful clot removal. The prediction of the angle of interaction on pretreatment imaging may help operators to select the most adequate mechanical thrombectomy technique on a case by case basis.